2009
DOI: 10.1163/156855509x412117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Linear, Branched and Hyperbranched Triphenylamine-Based Polyazomethines

Abstract: Novel triphenylamine-based linear, hyperbranched and branched conjugated polyazomethines have been synthesized by free-catalyst solution polycondensation of 1,4-diaminobenzene with 4,4 -diformyl triphenylamine, 4,4 ,4 -triformyl triphenylamine and their mixture in different molar ratios. Linear polyazomethine has a good solubility in organic solvents while branched and hyperbranched polymers are partially soluble. A wholly soluble hyperbranched polyazomethine was obtained by end-capping of polymer at gelation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Dioxane and tetrahydrofuran (THF) were dried on sodium wire and distilled under nitrogen just before use. 4-Formyl triphenylamine [22] and 4,4′,4′′-triformyl triphenylamine [2325] were obtained by formylation of TPA according to the reported methods. 4-Formyl-N,N′-bis(4-bromophenyl) aniline [26], tris (4-iodophenyl) amine [27] and vinyl triphenylamine [28] were synthesized and purified according to the literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Dioxane and tetrahydrofuran (THF) were dried on sodium wire and distilled under nitrogen just before use. 4-Formyl triphenylamine [22] and 4,4′,4′′-triformyl triphenylamine [2325] were obtained by formylation of TPA according to the reported methods. 4-Formyl-N,N′-bis(4-bromophenyl) aniline [26], tris (4-iodophenyl) amine [27] and vinyl triphenylamine [28] were synthesized and purified according to the literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…[19] In a previous paper, we have synthesized and characterized linear, branched, and hyperbranched polyimines (isoelectronic structure of PPVs) using bis-and tris-formyl triphenylamine and 1,4-diaminobenzene as condensation monomers. [20] We have observed that electronic conjugation in the hyperbranched polymers is more reduced than in linear polymers due to sterical hindrances; however, the aggregation of polymer chains in solution was not observed. As a continuation of this study, in this article, we report the synthesis of linear and branched PPVs and compare their optical, and electrochemical properties.…”
Section: Introductionmentioning
confidence: 88%
“…4,4′-Diformyl triphenylamine and 4,4′,4′′-triformyl triphenylamine were synthesized starting from triphe nylamine by formylation, according to the methods reported in the literature. [20][21][22] All solvents were commercially products and were used as received or purified or dried by known methods. 2.1.1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Niu et al [27][28][29] [31,32] have used 4,4 -diformyl-TPA in reaction with 4,4 -dioxyaniline, 4,4 -(1,3-phenylenedioxy)aniline or 1,4-phenylenediamine. We have also synthesized linear, branched and hyperbranched PAMs by solution polycondensation of bis-or trisaldehyde triphenylamine with aromatic diamines and studied the influence of chain architecture on their electrophysical properties [33]. All these materials are wholly aromatic polymers, have good solubilities and interesting electrophysical properties.…”
Section: Introductionmentioning
confidence: 99%